Recent trends on poverty, a gender perspective in Latin America - Damián, Araceli (Papeles de Población, 2021)
In this article I discuss the theoretical and methodological problems to incorporate gender into poverty measurement methods. I emphasise that gender cannot be considered as a constitutive element of poverty and, therefore, it cannot be incorporated as a variable in the poverty measurement methods. After that, I analyse whether there is a feminisation of poverty in Latin America based on two indicators. The fist one is the proportion of poor women with respect to poor men (adjusting this proportion to the relative weight each group represents on total population). The second one is the evolution of poverty by the gender of the household head between 1980 and 2000. Empirical evidence analysed refutes the idea of the feminisation of poverty. Finally, I analyse the improvement on some women’s social indicators (education, income and labour participation) during the 1980’s and 1990s, and the way this improvement has contributed to a reduction of gender inequalities.